Early pericalcarine atrophy in acute optic neuritis is associated with conversion to multiple sclerosis. Issue 9 (5th February 2011) - Jenkins, T M; Ciccarelli, O; Atzori, M; Wheeler-Kingshott, C A M; Miller, D H; Thompson, A J; Toosy, A T
Abstract : Background: Previous work showed that pericalcarine cortical volume loss is evident early after presentation with acute clinically isolated optic neuritis (ON). The aims of this study were: (1) to determine whether pericalcarine atrophy in patients with ON is associated with conversion to multiple sclerosis (MS); (2) to investigate whether regional atrophy preferentially affects pericalcarine cortex; and (3) to investigate potential causes of early pericalcarine atrophy using MRI. Methods: 28 patients with acute ON and 10 controls underwent structural MRI (brain and optic nerves) and were followed-up over 12 months. Associations between the development of MS, optic nerve, optic radiation and pericalcarine cortical damage measures were investigated using multiple linear regression models. Regional cortical volumetric differences between patients and controls were calculated using t tests. Results: The development of MS at 12 months was associated with greater whole brain and optic radiation lesion loads, shorter acute optic nerve lesions and smaller pericalcarine cortical volume at baseline. Regional atrophy was not evident in other sampled cortical regions. Pericalcarine atrophy was not directly associated with whole brain lesion load, optic radiation measures or optic nerve lesion length. However, the association between pericalcarine atrophy and MS was not independent of these parameters. Conclusions: Reduced pericalcarine cortical volumes in patients with early clinically isolated ON were associated with the development of MS but volumes of other cortical regions were not. Hence pericalcarine cortical regions appear particularly susceptible to early damage. These findings could be explained by a combination of pathological effects to visual grey and white matter in patients with ON.